The determinants that influence Hibah application in Kelantan (2022)
Hibah is an important instrument in estate planning according to Islamic law. a Hibah is a gift of property that occurs during the life of the giver of the Hibah. Hibah is a practice that is circumcised and encouraged in Islam especially to the immediate family. this practice is based on the Quran, sunnah and consensus. this instrument is encouraged in Islam, where if it is done correctly and in accordance with the requirements of sharia then it can avoid disputes and property disputes which are an issue that often occurs among muslims. this directly shows the importance of Hibah in the application of Hibah in daily life. the purpose of this study is to examine the determinants that influence the application of Hibah in Kelantan. in addition, the researcher has a specific research objective which aims to make this study focus on awareness, knowledge and attitude towards the application of Hibah that focuses among the community in Kelantan. the results of the analysis confirmed that there was a significant positive correlation between awareness, knowledge and attitude. the study used sever